All Days 2009
DOI: 10.2118/119569-ms
|View full text |Cite
|
Sign up to set email alerts
|

Are You Buying Too Much Friction Reducer Because of Your Biocide?

Abstract: Slickwater fracturing is a large portion of current stimulation treatments in tight gas reservoirs. The fluids typically contain only friction reducer and biocide. They are considered incredibly simple, with little attention paid to their composition beyond the effects of water quality. In many cases, the biocides are sold and added to the fluid stream by production chemical companies while the friction reducers are added by the service company performing the fracture treatment. The paper reviews the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Some biocides such as THPS and quaternary amines such as ADBAC appear to have adverse effects on friction reducers (Rimassa et al, 2009) These types of chemical additives interfere with the polymer hydration mechanism, impairing viscosity gains and resulting in loss of the friction reducer emulsion's ability to invert quickly. This interaction may create a higher tubular friction pressure during pumping, which may lead to using a higher loading of friction reducer the during treatment to maintain flow rate, thereby incurring a higher cost to achieve the same friction reduction, and subsequently increasing the potential for formation damage related to polymer residue.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…Some biocides such as THPS and quaternary amines such as ADBAC appear to have adverse effects on friction reducers (Rimassa et al, 2009) These types of chemical additives interfere with the polymer hydration mechanism, impairing viscosity gains and resulting in loss of the friction reducer emulsion's ability to invert quickly. This interaction may create a higher tubular friction pressure during pumping, which may lead to using a higher loading of friction reducer the during treatment to maintain flow rate, thereby incurring a higher cost to achieve the same friction reduction, and subsequently increasing the potential for formation damage related to polymer residue.…”
Section: Chemical Interactionsmentioning
confidence: 99%
“…For example, powder friction reducers suffer from slow dissolution, long mixing time, and complex mixing equipment, which restrict the supply capacity of slickwater and even affect the process of fracturing. Also, the solution of the powder product can be too viscous and stable, which makes it challenging to break. , The preparation process of a water-in-oil (W/O) emulsion friction reducer consumes a large amount of surfactants, and the existence of the oil phase causes formation damage such as a residual oil-soluble substance after gel breaking, treatment difficulty of flowback liquid, etc. A water-in-water (W/W) emulsion friction reducer is still in the laboratory development stage, and the product exhibits a low drag reduction. In addition, it is still inevitable that polymer will swell due to the existence of the water phase, which weakens the product stability, giving it fewer advantages for long-term storage and transportation. , …”
Section: Introductionmentioning
confidence: 99%
“…The polymers utilised in hydraulic fracturing operations depend on the environmental conditions. Anionic PAM have a better performance in a fresh water environment (Sun 2014;Rodvelt et al, 2015), whereas cationic PAM have demonstrated an enhanced performance at high salinity scenario (Rimassa et al, 2009;Nguyen et al, 2018). The potential advantages provided by friction reducer also include reduced chemical usage, fewer environmental concerns, and decreased water consumption (Geri et al, 2019).…”
Section: Introductionmentioning
confidence: 99%